ALLAMA IQBAL AND MAULANA ABUL KALAM AZAD’S THOUGHTS AND IDEAS ABOUT THE EXISTENCE AND SURVIVAL OF THE ISLAMIC STATE: IN THE CONTEXT OF LITERARY ASPECTS - Dr.Javed Iqbal Javed; Dr.Munnaza Munawer; Dr.Samia Ahsan; Dr.Muhammad Shouket Ali; Dr.Muhammad Haroon Qadir; Munazza Raheed; Dr.Sapna Mumtaz; Waseem Arshad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The thoughts of Iqbal and Azad have come to the mouths of witnesses in the light of the Qur’an and Hadith. The aim of both of them was to renew the Islamic nation and provide the materials for the renaissance of humanity by doing ijtihad in the religion of Islam. He arranged his thought on the basis of the Holy Quran and tried to find a solution to all the problems of the Islamic nation in the light of its teachings. The Muslims of the sub-continent are indebted to Iqbal and Azad for instilling determination in the veins of the Muslims here. Courage, will and courage, enthusiasm and passion, self-reliance and self-confidence and steadfastness and determination flowed. It is impossible to deny the fact that if we analyze the expressions accepted by these two important Urdu thinkers and writers in Islamic thoughts and affairs, then it will not be out of place to say that there is a difference in the style of expression between Iqbal’s poetry and the thoughts of Abul Kalam. In the same sense, Sajjad Ansari had said that if the Qur’an had been revealed in Urdu, Abul Kalam’s prose or Iqbal’s poetry would have been chosen for it.